A notion of stability in probability of stochastic nonlinear systems - Abedi, Fakhreddin; Leong, Wah June; Chaharborj, Sarkhosh Seddighi (SpringerOpen, 2013)
The concepts of stability in probability of nontrivial solutions for stochastic nonlinear systems are analyzed in terms of a control Lyapunov function which is smooth except possibly at the origin. We show under certain hypothesis that the neighborhood of the origin is stable in probability. An illustrating example is provided.